2018
DOI: 10.1177/1724600818764069
|View full text |Cite
|
Sign up to set email alerts
|

Lysine-specific demethylase 2A expression is associated with cell growth and cyclin D1 expression in colorectal adenocarcinoma

Abstract: Our study reveals a novel role for high-expressed KDM2A in colorectal adenocarcinoma cell growth, and that the expression of KDM2A is associated with that of cyclin D1 in colorectal adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
(35 reference statements)
1
8
0
Order By: Relevance
“…The flavin-dependent KDM family includes LSD1 (KDM1A/AOF2) and LSD2 (KDM1B/AOF1) [ 12 ]. LSD1 has been shown to be overexpressed in colorectal cancer and to promote the growth and invasion of colorectal cancer [ 16 , 17 ]. Although the function of LSD2 in the biology of other cancers such as breast cancer has been described in detail [ 15 ], the expression and function of LSD2 in CRC has not been reported until now.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The flavin-dependent KDM family includes LSD1 (KDM1A/AOF2) and LSD2 (KDM1B/AOF1) [ 12 ]. LSD1 has been shown to be overexpressed in colorectal cancer and to promote the growth and invasion of colorectal cancer [ 16 , 17 ]. Although the function of LSD2 in the biology of other cancers such as breast cancer has been described in detail [ 15 ], the expression and function of LSD2 in CRC has not been reported until now.…”
Section: Discussionmentioning
confidence: 99%
“…Although the effect of p53 on the role of the LSD family in colorectal cancer has been studied before, it remains controversial. Although it has been reported that LSD1 can regulate p53 by removing both monomethoxylation (k370me1) and dimerization (k370me2) at k370 [ 30 ], it has been reported that the expression of p53 is not related to LSD1 in CRC tissue [ 17 ].In our study, p53 was correlated with LSD2 function in CRC. We showed that LSD2 overexpression downregulated the protein levels of p53, while LSD2 knockdown upregulated p53.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KDM2A was first discovered in kidney COS-7 cells exhibiting robust histone demethylase activity (10). KDM2A was found to be highly expressed in lung (11), pancreatic cancer (12), colorectal adenocarcinoma (13), breast (14), gastric cancer (15) and certain blood diseases (16), which have been reported to be related to tumor aggressiveness and metastasis, chemotherapy resistance and poor prognosis. This protein has been linked to many signaling pathways, which promote cancer metastasis and malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…LSD2 has been noted to be overexpressed in several malignancies such as colorectal adenocarcinoma, small cell lung cancer and breast cancer [16, 17, 18]. Recent studies with breast cancer cell lines showed that overexpression of LSD2 led to increased cell proliferation and oncogenic transformation, but decreased cellular motility and invasion [15].…”
Section: Introductionmentioning
confidence: 99%